2017
DOI: 10.1088/1361-6463/aa8c23
|View full text |Cite
|
Sign up to set email alerts
|

Transparent arrays of silver nanowire rings driven by evaporation of sessile droplets

Abstract: A coffee-ring pattern can be yielded on the three-phase contact line following evaporation of sessile droplets with suspended insoluble solutes, such as particles, DNA molecules, and mammalian cells. The formation of such coffee-ring, together with their suppression has been applied in printing and coating technologies. We present here an experimental study on the assembly of silver nanowires inside an evaporating droplet of a colloidal suspension. The effects of nanowire length and concentration on coffee-rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[13] Self-assembled structures like the coffee-ring structure using evaporation could be applied to various research and industrial areas, such as transparent electrodes [14,15] and printing technologies. Deegan et al reported the coffeering effect that particles assembled by capillary and Marangoni flow inside the drying droplet.…”
mentioning
confidence: 99%
“…[13] Self-assembled structures like the coffee-ring structure using evaporation could be applied to various research and industrial areas, such as transparent electrodes [14,15] and printing technologies. Deegan et al reported the coffeering effect that particles assembled by capillary and Marangoni flow inside the drying droplet.…”
mentioning
confidence: 99%
“…There is no sign of the coffee-ring effect in the dried pixels. It was shown that large aspect-ratio particles, like Ag-NWs, produce strong capillary interactions that reduce the effect of accumulating particles in the liquid-air contact line [40,41]. These interactions, together with a fast-drying rate lead to a uniform distribution of the Ag-NWs along the whole pixel.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al have reported that AgNWs are subject to bending and aligning along the liquid-air interface of droplets. [50] Thus, in our printing technique, where the liquid-air interfaces were defined as hydrophilic/hydrophobic interfaces, AgNWs could be bent and aligned along the boundary lines on the edges of hydrophilic areas. However, few AgNWs remained on the hydrophobic areas ( Figure 3c); however, they are unconnected to the AgNW patterns.…”
Section: Discussionmentioning
confidence: 99%